2018
DOI: 10.3389/fmars.2018.00486
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-Related Thermal Stress Coupled With Upwelling-Related Ocean Acidification Negatively Impacts Cellular to Population-Level Responses in Pteropods Along the California Current System With Implications for Increased Bioenergetic Costs

Abstract: El Niño Negatively Impacts Pelagic Gastropods of a single parameter in the statistical analyses. High quantities of polyunsaturated fatty acids are susceptible to oxidative stress because of LPX, resulting in the loss of lipid reserves and structural damage to cell membranes, a potential mechanism explaining extreme pteropod sensitivity to low ar . Accumulation of oxidative damage requires metabolic compensation, implying energetic trade-offs under combined thermal and low ar and pH stress. Oxidative stress bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 69 publications
3
47
0
Order By: Relevance
“…Bednaršek et al () showed negative pteropod responses in the northern CCS to the 2013–2016 combined marine heat wave, El Niño, and enhanced upwelling. Aguilera et al () similarly observed reductions in growth and egg production in the resident copepod Acartia tonsa in the Humboldt Current System under warm, acidic conditions in 2015.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bednaršek et al () showed negative pteropod responses in the northern CCS to the 2013–2016 combined marine heat wave, El Niño, and enhanced upwelling. Aguilera et al () similarly observed reductions in growth and egg production in the resident copepod Acartia tonsa in the Humboldt Current System under warm, acidic conditions in 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The longest periods of consecutive aragonite undersaturation in our records during the Warm Anomaly and El Niño were significantly shorter than in 2011–2013 (see Table for values). Bednaršek et al () note that altered carbonate conditions have a dominant effect on pelagic mollusc health at the cellular level. The favorable carbonate conditions we observed likely provided some offset to thermal stress in 2014 and 2016, while moderate upwelling in spring 2015 produced less favorable carbonate conditions and may have negatively impacted organisms despite cooler temperatures and increased food availability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 While these calcifying organisms tend to be small in size and receive less conservation attention than larger fauna, they underpin many food webs in the region; a decline in marine calcifying organisms could have ripple effects on entire communities and ecosystems. 6,9,10 Beyond the ecological impacts of OA on calcifying organisms and their interrelated food webs, OA may wield significant economic impacts by placing additional pressures on fished species. OA impacts have been estimated for several important fishery species.…”
Section: Introductionmentioning
confidence: 99%